2020
DOI: 10.1186/s13287-020-01967-2
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of photobiomodulation-preconditioned diabetic stem cells accelerates ischemic wound healing in diabetic rats

Abstract: Background Diabetic foot ulcer is the most costly and complex challenge for patients with diabetes. We hereby assessed the effectiveness of different preconditioned adipose-derived mesenchymal stem cells (AD-MSCs) and photobiomodulation protocols on treating an infected ischemic wound in type 1 diabetic rats. Methods There were five groups of rats: (1) control, (2) control AD-MSCs [diabetic AD-MSCs were transplanted (grafted) into the wound bed], (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 56 publications
0
61
0
Order By: Relevance
“…Whereas our hypothesis (combined application of PBM and stem cells can accelerate repairing process and assist healing DFU in animal models and patients) was confirmed through preclinical studies [29,30,31], we suggest further animal and clinical trial investigations be conducted in order to provide more documentation. Hopefully these outcomes would help the use of ADSCs plus PBM as a routine treatment protocol for the healing of severe DFU in patients with DM.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Whereas our hypothesis (combined application of PBM and stem cells can accelerate repairing process and assist healing DFU in animal models and patients) was confirmed through preclinical studies [29,30,31], we suggest further animal and clinical trial investigations be conducted in order to provide more documentation. Hopefully these outcomes would help the use of ADSCs plus PBM as a routine treatment protocol for the healing of severe DFU in patients with DM.…”
Section: Discussionmentioning
confidence: 70%
“…Groups 2-5 displayed significantly increased wound strength compared to group 1.In most cases, group 5 had significantly better results than groups 2, 3, and 4. Ahmadi et al concluded that preconditioning diabetic ADSCs with PBM in vitro plus PBM in vivo significantly accelerated healing in the diabetic rat model of an ischemic infected delayed-healing wound [29]. In other related studies, the same results were reported.…”
Section: How the Combined Application Of Pbm And Adscs Can Accelerate Dfu Healingmentioning
confidence: 64%
See 1 more Smart Citation
“…MSCs, which are found in bone marrow and adipose tissue, have proven useful in wound healing applications. Recently, adipose-derived mesenchymal stem cells preconditioned by photobiomodulation, firstly in vitro and then followed by in vivo, were found to significantly improve healing rates of ischemic infected DFU in a rat model (Ahmadi et al, 2020). MSCs provide a great number of benefits, such as their ability to manage oxidative stress and promote an anti-inflammatory response and formation of new blood vessels in damaged tissues (Becerra-bayona et al, 2020).…”
Section: Stem Cellsmentioning
confidence: 99%
“…22 Photobiomodulation (PBM), as a treatment strategy, is expected to resolve the weak potential of transplantation and viability of ASC. 29 MSCs and progenitor cells are particularly susceptible to PBM. 30 It has been shown that PBM potentially promotes the proliferation, differentiation, and growth factor secretion of MSCs through altering gene expression and activation.…”
Section: Introductionmentioning
confidence: 99%